BAlN for III-nitride UV light-emitting diodes: undoped electron blocking layer. (12th February 2021) - Gu, Wen; Lu, Yi; Lin, Rongyu; Guo, Wenzhe; Zhang, Zihui; Ryou, Jae-Hyun; Yan, Jianchang; Wang, Junxi; Li, Jinmin; Li, Xiaohang
Abstract: The undoped BAlN electron-blocking layer (EBL) is investigated to replace the conventional AlGaN EBL in light-emitting diodes (LEDs). Numerical studies of the impact of variously doped EBLs on the output characteristics of LEDs demonstrate that the LED performance shows heavy dependence on the p-doping level in the case of the AlGaN EBL, while it shows less dependence on the p-doping level for the BAlN EBL. As a result, we propose an undoped BAlN EBL for LEDs to avoid the p-doping issues, which a major technical challenge in the AlGaN EBL. Without doping, the proposed BAlN EBL structure still possesses a superior capacity in blocking electrons and improving hole injection compared with the AlGaN EBL having high doping. Compared with the Al0.3 Ga0.7 N EBL with a doping concentration of 1 × 10 20 cm −3, the undoped BAlN EBL LED still shows lower droop (only 5%), compatible internal quantum efficiency (2% enhancement), and optical output power (6% enhancement). This study provides a feasible route to addressing electron leakage and insufficient hole injection issues when designing ultraviolet LED structures.